2015
DOI: 10.1007/s00406-015-0609-x
|View full text |Cite
|
Sign up to set email alerts
|

CACNA1C risk variant is associated with increased amygdala volume

Abstract: Genome-wide association studies suggest that genetic variation within L-type calcium channel subunits confer risk to psychosis. The single nucleotide polymorphism at rs1006737 in CACNA1C has been associated with both schizophrenia and bipolar disorder and with several intermediate phenotypes that may serve as neurobiological antecedents, linking psychosis to genetic aetiology. Amongst others, it has been implicated in alterations in amygdala structure and function. In the present study, we show that the risk a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 47 publications
(63 reference statements)
1
12
1
Order By: Relevance
“…1). The detected GM volume increase is consistent with the previous reports of larger total and regional GM volumes associated with the psychiatric risk A-allele carriers in European populations [Kempton et al, 2009;Wang et al, 2011;Lancaster et al, 2015]. However, our data indicate that the regional localization of this effect shows significant variations between studies, and increase in volume of risk A-allele carriers specially in prefrontal cortical, cingulate and temporal cortices in previous study [Wang et al, 2011] were not observed here.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…1). The detected GM volume increase is consistent with the previous reports of larger total and regional GM volumes associated with the psychiatric risk A-allele carriers in European populations [Kempton et al, 2009;Wang et al, 2011;Lancaster et al, 2015]. However, our data indicate that the regional localization of this effect shows significant variations between studies, and increase in volume of risk A-allele carriers specially in prefrontal cortical, cingulate and temporal cortices in previous study [Wang et al, 2011] were not observed here.…”
Section: Resultssupporting
confidence: 93%
“…Recent investigations in Europeans also suggest that allelic variation within the CACNA1C gene might be associated with psychopathology through modification of brain functions and structures. For example, the rs1006737 risk allele (A) has been associated with brain structure variations [Kempton et al, 2009;Perrier et al, 2011;Wang et al, 2011;Wolf et al, 2014;Lancaster et al, 2015], altered behaviors (e.g., reward responsiveness, semantic) [Krug et al, 2010;Strohmaier et al, 2013;Lancaster et al, 2014] as well as brain circuits involving working memory [Bigos et al, 2010;Dima et al, 2013;Heck et al, 2014;Paulus et al, 2014], episodic memory [Erk et al, 2010[Erk et al, , 2014aKrug et al, 2014 …”
mentioning
confidence: 99%
“…In healthy subjects, the CACNA1C risk allele (A-allele) at rs1006737 has been associated with increased hippocampal activity during emotional processing and increased prefrontal activity during executive cognition, specific patterns of brain activity that are associated with mental illness. 9 In addition, the risk allele have also been associated with higher psychopathology scores for depression and anxiety, 14 higher paranoid ideation scores, 15 increased activity in right amygdala during fear-face recognition, 16 and increased amygdala volume, 17 confirming the important role of this risk locus in the etiology of psychiatric traits.…”
Section: Introductionmentioning
confidence: 90%
“…Among the common SNP variants identified from the recent GWAS for example, variations in CACNA1C have been implicated as calcium signaling SNPs, found to confer the risk for schizophrenia [ 62 ]. Addressing this, several studies analyzed the calcium voltage-gated channel subunit α1 C-gene (CACNA1C) variations by the use of electrophysiological endophenotypes assessing phases of sleep in infants [ 64 ] by measuring regional gray matter volume [ 65 ], by measuring amygdale structure and/or function [ 66 , 67 ] by proton magnetic resonance spectroscopy of glutamatergic signals [ 68 ]. In the meanwhile, animal studies generate conditional knock-out mice for the analysis of calcium signaling in cellular level, linked to neuropsychiatric diseases [ 69 , 70 ].…”
Section: The New Agementioning
confidence: 99%